Hyperkeratosis and Frictional Dermatitis from Practicing Kendo - Masuki Yoshida; Naoki Oiso; Akira Kawada (Karger Publishers, 2010)
Repetitive mechanical activity induces a cutaneous reaction. A 22-year-old male presented with painful hyperkeratosis on the right heel. The hyperkeratosis had gradually developed after taking up the practice of Kendo. He also had slightly atrophic macules with scales on the left sole. We believe these lesions were caused by repeated stamping and friction during Kendo practice. Physical stresses can induce some types of skin disorders. We postulate that skin reactions caused by repetitive mechanical activity are more common than generally realized and that the interaction between physical activity and cutaneous reactivity must be examined more closely.